Determination of optimal pumping configuration for an L-band EDFA with 980-nm LD and ASE pumps - Adikan, Faisal Rafiq Mahamd; Mahdi, M.A.; Noor, A.S.M. (2003)
L-band gain improvement through amplified spontaneous emission (ASE) pumping was conducted. For an L-band amplifier system employing ASE to improve gain, pumping the system counter-directionally with ASE and codirectionally with 980 mn would yield the best overall performance in terms of gain. Gain improvement as high as 6 dB was attained. (C) 2003 Wiley Periodicals, Inc.